BORON K-EDGE XANES OF BORON OXIDES: TETRAHEDRAL B-O DISTANCES AND NEAR-SURFACE ALTERATION - Fleet M.E.; Liu X. (My University, 2001)
Synchrotron radiation boron K-edge XANES spectra collected in fluorescence yield mode are reported for monoclinic metaboric acid [HBO2(II)], sinhalite (MgAlBO4), and a selection of boron oxides in which B is exclusively in trigonal coordination ([3]B). The anomalously high divergence of tetrahedral ([4]B–O) bond lengths in HBO2(II) and sinhalite is used to resolve fine structure at the [4]B K edge due to splitting of σ*(t2) antibonding orbitals. For HBO2(II), XANES peaks at 196.9 and 199.3 eV are assigned to [4]B–O distances of 1.564 and ∼1.440 (3) , respectively, and, for sinhalite, peaks at 196.8, 197.9, and 199.6 eV are assigned to distances of 1.586, 1.483 (2), and 1.442 , respectively. A correlation between peak splitting at the [4]B K edge and divergence of tetrahedral bond length is established for borates and borosilicates using data for sinhalite, HBO2(II), ferroaxinite, danburite, datolite, and BPO4. B K-edge XANES spectra collected in total electron yield mode, which probes to [4]B in HBO2(II) and about one-third of the [4]B in sinhalite are converted to [3]B in the near-surface structure. Moreover, HBO2(II), HBO2(III), sassolite (boric acid; H3BO3), and v-B2O3, which have markedly different bulk structures, have a similar near-surface layer composed of a relaxed anhydrous network of BO3 groups.